2012
DOI: 10.1038/ng.2295
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey of recurrent HBV integration in hepatocellular carcinoma

Abstract: To survey hepatitis B virus (HBV) integration in liver cancer genomes, we conducted massively parallel sequencing of 81 HBV-positive and 7 HBV-negative hepatocellular carcinomas (HCCs) and adjacent normal tissues. We found that HBV integration is observed more frequently in the tumors (86.4%) than in adjacent liver tissues (30.7%). Copy-number variations (CNVs) were significantly increased at HBV breakpoint locations where chromosomal instability was likely induced. Approximately 40% of HBV breakpoints within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

76
931
6
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 797 publications
(1,034 citation statements)
references
References 29 publications
76
931
6
5
Order By: Relevance
“…Among these genes, ARID1A encodes a component of SWI/SNF chromatin remodelling complex and is also frequently mutated in HCC. In addition, genes encoding histone methyltransferase such as KMT2A/MLL, KMT2B/MLL2, KMT2D/MLL4 are also found mutated in eight ICC patients in this study, as reported in other cancer genome sequencing studies 12,19,54,59 . Among 102 ICC patients in our cohort, five (4.9%) harbours mutations in IDH1, and all mutations cluster in a previously reported hotspot (codon 132).…”
Section: Mutationsupporting
confidence: 66%
See 1 more Smart Citation
“…Among these genes, ARID1A encodes a component of SWI/SNF chromatin remodelling complex and is also frequently mutated in HCC. In addition, genes encoding histone methyltransferase such as KMT2A/MLL, KMT2B/MLL2, KMT2D/MLL4 are also found mutated in eight ICC patients in this study, as reported in other cancer genome sequencing studies 12,19,54,59 . Among 102 ICC patients in our cohort, five (4.9%) harbours mutations in IDH1, and all mutations cluster in a previously reported hotspot (codon 132).…”
Section: Mutationsupporting
confidence: 66%
“…Many large-scale genome sequencing projects have been executed to identify how somatic mutations [11][12][13][14][15][16][17][18] and hepatitis B virus (HBV) integration [19][20][21] affect HCC patients. In contrast, large-scale genome sequencing projects targeting the ICC cancer genomes just started to catch up.…”
mentioning
confidence: 99%
“…For HBV (a DNA virus), there is also evidence of viral integration, leading to expression of HBV-associated antigens in tumor cells (5)(6)(7). Early stage HCC can be cured by tumor ablation, resection, or liver transplantation, but most patients have more advanced disease at diagnosis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using next-generation sequencing technologies have highlighted the fact that, following the integration of HBV into the cellular genome, the 39-end of the HBx gene is often deleted and this event is observed more frequently in tumour tissues (Jiang et al, 2012;Sung et al, 2012;Toh et al, 2013). Furthermore, truncated HBx human chimeric transcripts may be seen and expressed as chimeric proteins (Sirma et al, 1999;Toh et al, 2013;Tu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These include hot-spot mutations in HBx at aa 130 and 131, which have been associated with the development of HCC (Iavarone et al, 2003;Kuang et al, 2004;Lee et al, 2011). Furthermore, the random integration of HBV DNA into the host genome frequently leads to 39-end-deleted sequences of the HBx gene and the observation of chimeric transcripts which often carry deletions at the 39-end of HBx gene, resulting in C-terminal-truncated HBx protein (Iavarone et al, 2003;Jiang et al, 2012;Ma et al, 2008;Sirma et al, 1999;Sung et al, 2012;Sze et al, 2013;Toh et al, 2013;Tu et al, 2001). Interestingly, a recent study with human HCC samples reports an association between the presence of C-terminal truncation of HBx and venous invasion (Sze et al, 2013).…”
Section: Introductionmentioning
confidence: 99%